Development of Multimedia Teaching Materials for PPKn Learning through a Design-Based Research Approach - Lie, Epifani R. Gunadi; Supriadi Supriadi; Alfi Mufida Rahmawati; Shellya Tanaya Dhayinta (Universitas Kristen Cipta Wacana, 2025)
The development of educational technology has driven the need for multimedia teaching materials that are more interactive, adaptive, and relevant to the characteristics of 21st-century students, especially in the subject of Pancasila and Citizenship Education ( PPKn ). In the field, teaching materials are still found to be static and have not been fully able to increase student learning engagement and critical thinking skills. This study aims to develop multimedia teaching materials for PPKn learning through a Design-Based Research (DBR) approach that focuses on the development, validation, and refinement of products iteratively based on user feedback. The research was conducted in four DBR stages needs analysis, design, development, and evaluation involving PPKn teachers , media experts, material experts, and high school students. The results of the study show that the developed multimedia teaching materials meet the feasibility indicators with very valid and very practical categories based on expert validation and limited field trials. In addition , the use of this teaching material has been proven to significantly increase learning motivation, student interaction, and understanding of citizenship concepts. The implications of the research emphasize the importance of integrating interactive technology in PPKn learning and the need for teacher training to optimize its implementation